Singuläre Störungsrechnung: 9.6. bis 15.6.1991 - Hale, Jack K.; Jäger, Willi; Modica, Luciano (Tagungsbericht, 1991)
Jack K. Hale; Ulrich Hornung; John A. Nohel; Olga A. Oleinik; Nicholas D. Alikakos; Guy Bouchitte; Lia Bronsard; Pavol Brunovsky; Giuseppe Buttazzo; Shui-Nee Chow; Bernold Fiedler; Dietrich Flockerzi; Irene Fonseca; Leonid S. Frank; Giorgio Fusco; Frank C. Hoppensteadt; Willi Jäger; Bernd Kawohl; James P. Keener; Klaus Kirchgässner; Christian Klingenberg; Hans Wilhelm Knobloch; Dietmar Kröner; Stephan Luckhaus; John Mallet-Paret; Moshe Marcus; Alexander Mielke; Konstantin Mischaikow; Luciano Modica; Yasumasa Nishiura; Robert E. O'Malley, Jr.; Genevieve Raugel; Hans-Görg Roos; Kunimochi Sakamoto; Jan A. Sanders; Klaus R. Schneider; Donald Smith; Luc Tartar; Yingfei Yi; Wen-an Yong
Keywords: Konferenzschrift